2008
DOI: 10.2134/jeq2006.0208
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in 2‐Methyl‐4‐chlorophenoxyacetic Acid Mineralization and Sorption in a Sandy Soil at Field Level

Abstract: The phenoxyacetic acid herbicide MCPA (2-methyl-4-chlorophenoxyacetic acid) is frequently detected in groundwater beneath Danish agricultural fields. We investigated spatial variation in microbial MCPA mineralization potential in a flat agricultural field of fine sandy soil (USDA classification: Humic Dystrudept) located on the Yoldia plains of Northern Jutland, Denmark. Samples for determination of MCPA mineralization and sorption were collected from the Ap and Bs horizons at 51 sampling sites located in a 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…Consistent decline in average pesticide biodegradation rate with increasing soil depth has been reported for diverse compounds (Larsen et al, 2000 ; Rodriguez-Cruz et al, 2006 ; Stenrød et al, 2006 ; Gaultier and Farenhorst, 2007 ; Fredslund et al, 2008 ; Rodriguez Cruz et al, 2008 ; Shymko and Farenhorst, 2008 ; Badawi et al, 2013b ). This reduction in mineralization potential is detectable over relatively short vertical distances from the plow layer and into the subsoil, but sometimes extends down to the underlying aquifer (Batıoğlu-Pazarbaþı et al, 2012 ), and follows a general trend similar to that of total bacterial biomass (Holden and Fierer, 2005 ).…”
Section: Scale and Extent Of The Spatial Variability Of Biodegradatiosupporting
confidence: 56%
See 1 more Smart Citation
“…Consistent decline in average pesticide biodegradation rate with increasing soil depth has been reported for diverse compounds (Larsen et al, 2000 ; Rodriguez-Cruz et al, 2006 ; Stenrød et al, 2006 ; Gaultier and Farenhorst, 2007 ; Fredslund et al, 2008 ; Rodriguez Cruz et al, 2008 ; Shymko and Farenhorst, 2008 ; Badawi et al, 2013b ). This reduction in mineralization potential is detectable over relatively short vertical distances from the plow layer and into the subsoil, but sometimes extends down to the underlying aquifer (Batıoğlu-Pazarbaþı et al, 2012 ), and follows a general trend similar to that of total bacterial biomass (Holden and Fierer, 2005 ).…”
Section: Scale and Extent Of The Spatial Variability Of Biodegradatiosupporting
confidence: 56%
“…In surface soil, pesticide degradation potential can be characterized by low coefficients of variation, either because the pesticide is homogeneously poorly degraded [e.g., metribuzin and triazinamin in Vinther et al ( 2008 )] or because it is readily degraded in most samples [e.g., MCPA in top soil samples collected both at the field scale and across a few cm 2 (Fredslund et al, 2008 ; Badawi et al, 2013b )]. High CVs, often exceeding 40%, are associated with pesticides that show contrasting degradation potential across the sampled area [e.g., glyphosate (Vinther et al, 2008 ), linuron (Rasmussen et al, 2005 ), and isoproturon (Rodriguez-Cruz et al, 2006 )].…”
Section: Scale and Extent Of The Spatial Variability Of Biodegradatiomentioning
confidence: 99%
“…This confirms our hypothesis that litter addition together with MCPA favours the proliferation of the MCPA-degrading community and, thus, MCPA degradation at a larger scale. Our results are in line with the study of Fredslund et al (2008) who found that MCPA degradation in the field strongly depended on growth conditions for MCPA degraders.…”
Section: Mcpa-degrading Communitysupporting
confidence: 93%
“…MCPA and mecoprop are extensively used in varying land uses across Ireland. Based on MCPA's low sorption and relatively high water solubility, the herbicide is potentially mobile, especially in soils with low organic carbon contents (Fredslund et al 2008;Hiller et al 2006). MCPA is not attenuated in deeper soil layers which renders it a threat to groundwater quality (Sørensen et al 2006) should it reach that far.…”
Section: Frequency Of Pesticidesmentioning
confidence: 99%